2008
DOI: 10.1007/s12275-008-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of marine birnavirus in cultured olive flounder Paralichthys olivaceus in Korea

Abstract: Surveys of marine birnavirus (MABV) were undertaken in cultured olive flounder Paralichthys olivaceus from the south and west coastal areas and Jeju in Korea during the period January 1999 to April 2007. MABV was detected in all seasons from the fry, juveniles and adult fish from the areas examined. Evident cytopathic effects of the virus including rounding and cell lysis were observed in chinook salmon embryo (CHSE-214) and rainbow trout gonad (RTG-2) cells, but not in fathead minnow (FHM) and epithelial papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…1). 6,20 Genogroup I included strains from Canada, the United States, and Japan; genogroup II included isolates from Denmark, Taiwan, and Japan; genogroup III included isolates from France, Norway, Thailand, England, and Denmark; genogroup IV included isolates from Canada and England; genogroup V included Canadian isolates; genogroup VI included German isolates; and genogroup VII was composed of Korean isolates (FJ, FK, FWA, NC1, FM2, and DS) from cultured olive flounder and Japanese isolates from marine fish and molluscan shellfish. Seven isolates in the current study were classified into genogroup VII and were closely related to isolates from Korean and Japanese coastal areas.…”
Section: Research-article2013mentioning
confidence: 99%
“…1). 6,20 Genogroup I included strains from Canada, the United States, and Japan; genogroup II included isolates from Denmark, Taiwan, and Japan; genogroup III included isolates from France, Norway, Thailand, England, and Denmark; genogroup IV included isolates from Canada and England; genogroup V included Canadian isolates; genogroup VI included German isolates; and genogroup VII was composed of Korean isolates (FJ, FK, FWA, NC1, FM2, and DS) from cultured olive flounder and Japanese isolates from marine fish and molluscan shellfish. Seven isolates in the current study were classified into genogroup VII and were closely related to isolates from Korean and Japanese coastal areas.…”
Section: Research-article2013mentioning
confidence: 99%
“…These viral infections can also be found in association with other bacteria ( Streptococcus iniae, Edwardsiella tarda and Vibrio spp. including V. harveyi , V. fischeri, V. alginolyticus, V. splendidus, V. ichthyoenteri ) or other viral pathogens (viral nervous necrosis virus [VNNV], viral haemorrhagic septicaemia virus [VHSV], lymphocystis disease virus), which results in higher mortalities (Jung et al, ; Oh et al, ; Pakingking et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies reported earlier were focused on gene expression analysis of single pathogen and specifically defined the expression pattern of limited genes [32][33][34][35][36] . Further, infection by two or more pathogens were reported in the olive flounder genome 37,38 . In order to solve these problem, we need plentiful genomic information to respond rapidly to multiple infection of pathogens.…”
mentioning
confidence: 99%